Microstructural stability of nanostructured fcc metals during cyclic deformation and fatigue - Funk, Matthias Friedrich (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2012)
Nanostructured metals with maximal grain or twin sizes of less than 100 nm have advanced properties like increased strength.As beneficial as these microstructures can be for the strength of materials, they are not infinitely stable. During mechanical loading these metals tend to coarsen and lose their beneficial structure. Besides electron microscopic analysis of fatigued samples, in situ cycling tests were conducted in order to observe structural degradation during mechanical loading.